Rana temporaria Linneaus 1758 ... - Elmberg, Johan (Zenodo, 2023)
Common Frog Rana temporaria Linneaus 1758 Distribution (Figure 5). Included records from Artportalen (N=2000): a ubiquitous species for which all reported records have been included.Any rare confusion with Rana arvalis would not change the overall picture of distribution or abundance. Widespread and abundant throughout the Southern Boreal, Middle Boreal, Northern Boreal regions, and in the Subalpine life zone. Widespread and locally common in the Low-Alpine zone. Scattered occurrences in the Mid-Alpine zone (Figures 15, 16). Breeding sites in the Low-Alpine zone reach at least 840 m altitude in Lycksele lappmark (Elmberg 1991; Figure 17) and probably up to or above 1000 m further south in the Scandic Mountains. In other words, it is a widespread breeder well above treeline. In summertime adults have been observed at 1070 m in Åsele lappmark and Lycksele lappmark, and at up to 1400 m in Jämtland (Helagsfjället), all of which are in the upper part of the Mid-Alpine zone. Occurrence and reproduction are known ... : Published as part of Elmberg, Johan, 2023, Amphibians and reptiles in North Sweden: distribution, habitat affinities, and abundance (Classes: Amphibia and Reptilia), pp. 301-335 in Zootaxa 5301 (3) on pages 312-313, DOI: 10.11646/zootaxa.5301.3.1, http://zenodo.org/record/8030434 ...